The Role of Savings and Loan Cooperatives in Efforts to Develop Micro, Small, And Medium Enterprises (MSMEs), Especially in Fostered Vegetable Business Field KSP Kopdit Hiro Heling - Yohanes Bosko Beding; Henrikus Herdi; Wihelmina Maryetha Yulia Jaeng; Marselus Don Bosko (Neo Journal of economy and social humanities, 2024)
This research aims to optimize the role of savings and loan cooperatives in efforts to develop micro, small, and medium enterprises, especially in the field of vegetable business fostered by KSP. Kopdit Hiro Heling. In this study, qualitative data is used, namely data in the form of words or non-numbers. The qualitative data used in this study were obtained through interviews and observations. The analysis technique used in this study is by using an interactive analysis model. This model is used to dig up information about the credit risk that occurs. The results of the study show that KSP Kopdit Hiro Heling has a strategic position in developing the economic potential of its members through the provision of business capital, training, and marketing support. With a comprehensive strategy, this cooperative helps its members increase productivity, competitiveness, and business sustainability. KSP Kopdit Hiro Heling also has a significant role in improving the quality of life of its members through skills training, family economic stability, and collaboration support with external parties. These cooperatives not only meet basic economic needs but also help their members achieve personal success and social well-being.